Human Rights And Freedoms Under The Conditions of Martial State: Legal Regulation, Directions of Improvement - Pavlo Liutikov; Wiktor Branowicki; Olga Shchypanova; Serhii Yehorov; Oleksiy Ulyanov (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The crisis in Ukraine, sparked by Russia's intervention in March 2014 and culminating in February 2022, has had a profound impact on human rights not only in Ukraine but also in European Union member nations. It is substantiated that human rights are an effective tool for limiting public power, which prevents its arbitrary action. This attribute makes human rights a distinguishing feature of a democratic state-legal regime, as opposed to authoritarian and totalitarian regimes, which do not accept the natural nature of these rights and identify them with their own will. Protecting human rights under martial law is extremely difficult. The difficulty lies in the fact that protecting human rights under martial law is not an easy task. Therefore, the development of mechanisms for the protection of human rights is a key step in ensuring justice, the development of democracy, and the development of mechanisms for the protection of human rights is particularly important for ensuring justice, the development of democracy and the restoration of peace in our country. A legitimate state must protect people's and citizens' rights and liberties. Even during conflict in a democratic state, it is difficult to abdicate the responsibility to protect human rights. Given the basic nature of this issue, it is vital to control it on a constitutional and legal level. According to Article 3 of the Constitution of Ukraine, the state has an obligation to ensure human rights, which determines the direction of its activity and functional orientation. The state is responsible for the realization and affirmation of human rights. Therefore, martial law cannot be used to waive the obligation to ensure human rights. The Constitution of Ukraine also contains provisions that determine the specifics of the implementation of individual human rights in the conditions of martial law.